Penyuluhan Mengenai Pentingnya Posyandu untuk Bayi dan Balita di Posyandu Mawar Indah RW 07 KP. Cikatuncar Kelurahan Kotabaru Kota Tasikmalaya - Alma Aulia Saphira; Santi Shopiyah; Zilfa Auliyaa Faidah; Risma Amelia Putri; Syahla Rahmah Ainun Nisa; Fajar Permana; Andy Muharry (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Based on the record owned by the cadre, there are currently 97 babies and toddlers. However, the attendance rate of mothers and toddlers at the Mawar Indah Posyandu (integrated health service post) averages only 35% each month. This low attendance rate attracted researchers to initiate a community counseling program with goals to increase awareness and participation among mothers of infants and toddlers in the area. The approach to community empowerment adopted in this study is centered on a public health education campaign, highlighting the critical role of Posyandu in supporting the growth and development of infants and toddlers. The initiative included key steps starting with presenting the benefits of Posyandu for children's growth and developments, engaging participants in a discussion session, and providing door prizes as incentives. The result of the outreach program is attended by 28 mothers along with their children. However, at this level of attendance achieved an average at 28.8%, falling short of the defined success indicators and lower than the previous rate. This outcome was influenced by several factors as outlined in H.L. Bloom’s theory, including environmental factors, individual behavior, healthcare services, and genetic predispositions. The findings indicate that despite efforts to increase awareness and participation, the involvement of mothers with infants and toddlers in the area remains insufficient. Contributing factors include environmental, behavioral, and healthcare service factors. To achieve more optimal results, improvements in these aspects are essential to increase maternal participation in Posyandu programs.